PENGARUH METODE PENGOLAHAN TERHADAP PENETAPAN KADAR AKRILAMIDA PADA POPCORN SECARA KROMATOGRAFI CAIR KINERJA TINGGI - Iswandi, Iswandi; Roshinta Wulandari, Sasongko; Anita Nilawati (Journal Pharmactive, 2023)
Acrylamide is a compound that is known to cause cancer and is potentially carcinogenic in humans. Acrylamide is formed in foods that contain carbohydrates and proteins when exposed to high temperature. One popular food that has the potential to generate acrylamide is popcorn. This research aims to determine the levels of acrylamide in popcorn using different processing methods, namely frying and baking, through High Performance Liquid Chromatography. Popcorn samples were obtained from the frying and oven method at 1560C. Sample preparation was carried out by extraction technique using dichlormethane and ethanol solvents. Acrylamide analysis was performed using High Performance Liquid Chromatography method with column C18, UV – Vis detector, wavelength 210 nm, mobile phase of 85% phosphoric acid in acetonitrile : aquabidest (5 : 95) and flow rate of 0.5 mL/min. Acrylamide testing begins with method validation including linearity, LOD, LOQ, accuracy and precision along with the determination of acrylamide levels. Data analysis using SPSS with the Shapiro – Wilk method and Independent Sample t – test. Based on the research, it was found that the results of method validation on the linearity coefficient were 0.999, the LOD test obtained 0.3933 ppm and LOQ 1.1918 ppm. The accuracy test obtains a recovery value of 97.29% and a precision value of 1.36%. Acrylamide levels for fried popcorn samples obtained an average level of 0,0417 g/kg. Acrylamide levels for oven popcorn samples obtained an average level of 0,0501 g/kg. The results of this study showed that there was no significant difference between fried popcorn and oven popcorn as evidenced by the SPSS test with a sig value of > 0.05.